2009
DOI: 10.1287/mnsc.1090.1021
|View full text |Cite
|
Sign up to set email alerts
|

Relative Performance Compensation, Contests, and Dynamic Incentives

Abstract: Contests (or tournaments) are pervasive in organizations. They help performance evaluation by eliminating common shocks affecting agents' performance. However, tournaments are less effective when participants have heterogeneous ability because participants may conclude that the ability gap is too large to be overcome by their effort. Our theoretical analysis shows that a similar loss of motivation arises when tournaments take place over multiple periods because interim performance acts in a way that is similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(110 citation statements)
references
References 22 publications
5
100
1
Order By: Relevance
“…For example, Garcia and Tor () show that average test scores decreased with the number of test takers and that average test times decreased when subjects believed they were taking the test with fewer other participants. Closer to questions of heterogeneity, Casas‐Arce and Martínez‐Jerez () find that in a dynamic multiperiod contest, leaders decrease their effort when their lead in a given period extends. Boudreau, Lacetera, and Lakhani () study an order‐statistic mechanism whereby adding competitors increases the observed range and dispersion of solutions through an increase in the number of “draws.” That research shows that this effect increases with increased problem‐solution uncertainty.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Garcia and Tor () show that average test scores decreased with the number of test takers and that average test times decreased when subjects believed they were taking the test with fewer other participants. Closer to questions of heterogeneity, Casas‐Arce and Martínez‐Jerez () find that in a dynamic multiperiod contest, leaders decrease their effort when their lead in a given period extends. Boudreau, Lacetera, and Lakhani () study an order‐statistic mechanism whereby adding competitors increases the observed range and dispersion of solutions through an increase in the number of “draws.” That research shows that this effect increases with increased problem‐solution uncertainty.…”
Section: Related Literaturementioning
confidence: 99%
“…Given the widespread use of tournaments in the economy and potentially different objectives of tournament sponsors, these policies provide useful “levers” for tournament designers. For example, sales managers may run contests with the goal of maximizing total sales (Casas‐Arce and Martínez‐Jerez, ), whereas those managing a research and development tournament may only be concerned with attracting the best possible solution (Fullerton and McAfee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Organizations create competitive interdependence by rewarding relative performance, so that the superior performance of an employee produces rewards for that individual but leaves other employees worse off. Such reward systems may be used to stimulate performance in a number of domains of organizational activity (Becker & Huselid, 1992;Casas-Arce & Martínez-Jerez, 2009). For example, employees working in sales may receive bonuses such that only the highest performer or a few employees with the highest performance receive a bonus.…”
Section: Interdependence and Perceived Instrumentality Of Competent Cmentioning
confidence: 99%
“…We thank an anonymous reviewer for raising this point. Martínez-Jerez, 2009;Harbring & Irlenbusch, 2008;Kalra & Mengze, 2001). To continue the sports metaphor, the interorganizational analogy to the tournament may be the "tryout" (Lazear & Rosen, 1981).…”
Section: Implications For Theorymentioning
confidence: 99%